Intraoperative autotransfusion. Experience in 725 consecutive cases. - Keeling, M M (1983)
Autologous intraoperative transfusion employing the Haemonetics Cell Saver is reported in 725 patients from a general hospital population, of which 75% were cardiovascular patients. The remaining cases included various orthopedic procedures, splenectomy, craniotomy, ectopic pregnancies, Caesarian sections, and exploratory laparotomy. On occasion, this method was utilized in trauma and in pediatric surgery. The product of washed red blood cells gave an average yield of 573 cc per case with an average hematocrit of 55 cc/dl available for autologous infusion. In 100 consecutive open heart procedures operated prior to the Cell Saver period, an average of 1.97 units of bank blood was utilized during operation, as compared with 0.75 units in 100 consecutive cases studied employing the Cell Saver (p less than 0.0001). Homologous blood utilization during cardiac surgery declined more than 50% with the use of the Cell Saver. Quality control was monitored scrupulously and included special precautions against air embolism, abnormal coagulation, and sepsis. The overall mortality rate was 2.8%, and in no instance was mortality or morbidity ascribable to the autologous transfusion. Numerous advantages offered by autotransfusion include prevention of sensitization of the recipient to various antigens in donor erythrocytes, leucocytes, platelets, and plasma, and avoidance of transfusion-transmitted diseases, especially viral hepatitis. Additionally, autologous blood, the only perfectly compatible product, provided immediate availability while conserving blood bank resources. In circumstances in which the intraoperative blood loss exceeded 1000 cc in the adult, its use was observed to be cost-effective. In the present study, autotransfusion proved safe, efficient, and in some instances life saving.